THE ROLE OF ALTERNARIA ALTERNATE IN THE BIOACCUMULATION OF TWO TYPES OF POLYMERIC WASTE - badr, Sanaa qasem (Antis-Publisher, 2024)
The fungus (Alternaria alternate ) was isolated from Abu Al-Khasib soil samples, and after obtaining pure isolates of the fungus, the fungus was grown with pieces of polymeric waste films of two types (PMMA & PS) and at different incubation periods (15 , 30, and 45 days ). After each incubation period, the weight of the piece was measured, and the result was a decrease in weight as the incubation period increased. Thus, the role of the fungus was to decrease Weight because fungi play a major role in the bioaccumulation process